The SIRT7-nucleolus connection in cancer: ARF enters the fray - Shahriar Tarighi; Poonam Kumari; Alejandro Vaquero; Thomas Braun; Alessandro Ianni (Molecular & Cellular Oncology)
The nucleolar enzyme sirtuin 7 (SIRT7) promotes cancer progression in certain malignancies, likely in part by controlling ribosome biosynthesis. Recently, we discovered that SIRT7 destabilizes the cyclin dependent kinase inhibitor 2A (CDKN2A, known as ARF) within the nucleolus, aiding cancer progression. We propose that targeting nucleolar SIRT7 offers promise for new anti-cancer therapies.